The Role Of Digital Marketing-Based Marketing Communications In Attracting Millennials And Gen Z To Pekanbaru Agro Tourism - Dewi, Susi Artuti Erda; Yodiansyah, Hefri; Jummaulana, Harry (Doctoral Program of Social Science Pasundan University, 2025)
The development of digital technology has changed the way tourist destinations interact with their audiences, particularly millennials and Gen Z, who dominate internet users in Indonesia. This study aims to analyze the role of digital marketing communications in increasing the interest of young people to visit Pekanbaru Agro Tourism. The study used a descriptive qualitative approach with a purposive sampling technique with five informants, consisting of owners, employees, and visitors. Data were collected through observation, semi-structured interviews, and documentation of social media content, then analyzed using reduction, presentation, and conclusion techniques. The results show that the use of Instagram and TikTok plays a dominant role in attracting the attention of the younger generation through visual, educational, and interactive content. Millennials are more responsive to Instagram, while Gen Z shows a significant increase in TikTok. Digital marketing strategies have been proven to increase engagement, strengthen the destination's image, and encourage visitor loyalty through two-way interactions. The study's conclusions emphasize that digital marketing communications function not only as a promotional tool but also as a medium for interaction and the formation of a positive destination image. The practical implications of this study provide recommendations for tourism managers to optimize creative content-based digital marketing strategies according to the characteristics of young audiences.